On the geochemical heterogeneity of rivers draining into the straits and channels of the Canadian Arctic Archipelago. Issue 10 (12th October 2017) - Alkire, Matthew B.; Jacobson, Andrew D.; Lehn, Gregory O.; Macdonald, Robie W.; Rossi, Matthew W.
Abstract: Ten rivers across northern Canada and the Canadian Arctic Archipelago (CAA) were sampled during spring 2014 and summer 2015 to investigate their geochemical heterogeneity for comparison against larger North American (i.e., Mackenzie and Yukon Rivers) and Siberian rivers. In general, rivers draining the western and/or northern regions of the study area have higher solute concentrations and lower 87 Sr/ 86 Sr ratios compared to rivers draining the eastern and/or southern regions. The inorganic geochemical signatures largely reflect the bedrock geology, which is predominately carbonate in the western and/or northern regions and silicate in the eastern and/or southern regions. Riverine δ 18 O values primarily correlate with latitude, with only a few exceptions. Measurements of total alkalinity (TA) were combined with a regional analysis of bedrock geology and extrapolated to produce a range for the mean characteristic TA of rivers draining into the straits and channels of the CAA (628–819 µeq kg −1 ). Combining this estimate with contributions from the Mackenzie River yields a revised North American river runoff TA of 935–1182 µeq kg −1, which is much lower than that of the Mackenzie River (1540 µeq kg −1 ). This lower concentration suggests that TA may not be used to distinguish between North American and Siberian river contributions in regions such as Davis Strait. Key Points: Ten rivers across the Canadian Arctic were sampled to investigate geochemical differences compared to larger North American rivers Inorganic geochemistry reflected bedrock geology, which is mostly carbonate in the west/north and mostly silicate in the east/south Discharge of small Canadian Arctic rivers is ~260 km 3  yr −1 with an average total alkalinity of 628‐819 µeq kg −1